2020
DOI: 10.1039/d0ee02959a
|View full text |Cite
|
Sign up to set email alerts
|

Solar water splitting exceeding 10% efficiencyvialow-cost Sb2Se3photocathodes coupled with semitransparent perovskite photovoltaics

Abstract: Solar water splitting directly converts solar energy into H2 fuel that is suitable for storage and transport. To achieve a high solar-to-hydrogen (STH) conversion efficiency, elaborate strategies yielding a high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 39 publications
0
45
1
Order By: Relevance
“…water splitting with a wide range of semiconductor materials including a metal chalcogenide (Sb 2 Se 3 ), a metal oxide (Cu 2 O), and single crystalline Si. Beginning with photocathodes based on Sb 2 Se 3 , which is an emerging light absorbing semiconductor for PEC water splitting [13][14][15][16][17][18][19] and solar cells, [20][21][22][23][24] it is successfully shown that each functional layer and interface in the multi-layered photocathodes can be investigated under operando conditions depending on the frequency domain at which the photophysical/electrochemical processes occur. The carefully verified model allows us to obtain in-depth information about the TiO 2 layer as well as the Sb 2 Se 3 layer (e.g., depletion layer thickness, carrier densities, charge carrier lifetimes under different light intensities and applied potentials), and to compare it with those data obtained by the EIS analysis of Cu 2 O and Si photocathodes.…”
Section: Introductionmentioning
confidence: 99%
“…water splitting with a wide range of semiconductor materials including a metal chalcogenide (Sb 2 Se 3 ), a metal oxide (Cu 2 O), and single crystalline Si. Beginning with photocathodes based on Sb 2 Se 3 , which is an emerging light absorbing semiconductor for PEC water splitting [13][14][15][16][17][18][19] and solar cells, [20][21][22][23][24] it is successfully shown that each functional layer and interface in the multi-layered photocathodes can be investigated under operando conditions depending on the frequency domain at which the photophysical/electrochemical processes occur. The carefully verified model allows us to obtain in-depth information about the TiO 2 layer as well as the Sb 2 Se 3 layer (e.g., depletion layer thickness, carrier densities, charge carrier lifetimes under different light intensities and applied potentials), and to compare it with those data obtained by the EIS analysis of Cu 2 O and Si photocathodes.…”
Section: Introductionmentioning
confidence: 99%
“…Though acidic media can maximize the performance of photocathodes when they are coupled with a noble metal anode, there is still no earth‐abundant anode material that can survive in an acidic environment. [ 2d,27 ] In this respect, our PEC‐PV tandem device, consisting of alkaline‐resistive and non‐precious metal‐based (photo)electrodes, can provide a new promising way for efficiently converting solar energy to hydrogen molecules.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7][8] Thin lms of antimony selenide have also been successfully used as photocathodes for the hydrogen evolution reaction. [9][10][11] These achievements motivate further exploration of low-cost and straightforward deposition methods of this material, such as deposition methods based on the thiol : amine "alkahest" solution inks. Yet, to facilitate further progress and utility of these inks for these applications, the connection between the processing method of the materials Fig.…”
Section: Introductionmentioning
confidence: 99%